Pengaruh Investasi Dan Tenaga Kerja Terhadap Pertumbuhan Ekonomi Di Provinsi Jambi - Desmetika Desmetika; Ambok Pangiuk; Muhamad Subhan (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The ideal economy is an economy that continues to develop without experiencing a decline for a year or even a quarter. In line with this, the economy will create stable value conditions and open up extensive employment opportunities. However, in reality, financial conditions generally experience ups and downs. The aim of this research is to find out how partially or simultaneously investment and labor influence economic growth. In this research, researchers used the Quantitative Descriptive method. The analysis techniques used are Data Quality Test, Classic Assumption Test, Hypothesis Test, Multiple Linear Regression Analysis and Coefficient of Determination. The research results show that: investment (X1) has no significant effect on economic growth. Labor (X2) has a significant effect on economic growth. Investment (X1) and labor (X2) simultaneously have an insignificant effect on economic growth (Y).